Higher Fashion Education in Perspective: The Effects of Work-Based Learning On Industry Requirements (British Journal of Multidisciplinary and Advanced Studies, 2023)
Change occurs rapidly in the world of work these days. Keeping pace with this rapid change is a continuing challenge for Ghana’s Higher Education (HE) institutions. The study, thus, explored the effects of work-based learning (WBL) on industry requirements through higher fashion education in Ghana. The research adopted the quantitative data collection and analysis method. The population for the study comprised postgraduate and undergraduate students of the HE institution in Ghana, offering the fashion design and textiles option as well as fashion houses (industry). The data was analysed using the hierarchical multiple regression statistical technique. Regarding policy, the findings may be used to inform decisions related to the curriculum of fashion design and textile programmes in Ghana. In terms of research, it provides evidence of the positive impact of WBL experiences on students’ preparedness for the fashion industry.